TRADISIONALISME-PROGRESIF HUKUM PERNIKAHAN ANAK: (STUDI FATWA KONGRES ULAMA PEREMPUAN INDONESIA) - Bazikh, Moh. Rofqil (Syakhsia Jurnal Hukum Perdata Islam, 2024)
The various negative impacts of early marriage do not necessarily make this problem immediately handleable. At the same point, Law No. 1/1974 and Law No. 16/2016 also cannot overcome early marriage optimally. The opening of legally valid early marriage dispensation opportunities is one of the reasons. This article will discuss the law of early marriage in the fatwa of the Indonesian Women's Ulama Congress (KUPI). However, the focus of this article is not on the normative level of early marriage. Rather, this article will discuss the style of KUPI's thinking in formulating fatwas related to this topic. This research is qualitative-descriptive, with research anchored in library research. Primary data was obtained from the Official Documents of the Process and Results of the First Indonesian Women Ulema Congress (KUPI). Secondary data is taken from articles, journals, and books with relevant topics. To discuss the findings, the typology of Islamic thought styles and trends initiated by Abdullah Saeed is used. The conclusion reached in this study is that KUPI's religious deliberations adopt two styles proposed by Saeed. Both legalist traditionalist and progressive ijtihadist are found in KUPI's fatwas. Thus, one foot of KUPI is grounded in the traditional treasures, while the other foot goes in a progressive direction. The conclusion about the combination of these two styles comes after first discussing the arguments and analysis put forward by KUPI.